Analgesia by inhibiting tetrahydobiopterin synthesis - Costigan, Michael (2011)
Physiological control of the co-factor tetrahydrobiopterin (BH4) is tight in normal circumstances but levels increase pathologically in the injured somatosensory system. BH4 is an essential co-factor in the production of serotonin, dopamine, epinephrine, norepinephrine and nitric oxide. Excess BH4 levels cause pain, likely through excess production of one or more of these neurotransmitters or signaling molecules. The rate limiting step for BH4 production is GTP Cyclohydrolase 1 (GCH1). A human GCH1 gene haplotype exists that leads to less GCH1 transcription, translation, and therefore enzyme activity, following cellular stress. Carriers of this haplotype produce less BH4 and therefore feel less pain, especially following nerve injury where BH4 production is pathologically augmented. Sulfasalazine (SSZ) an FDA approved anti-inflammatory agent of unknown mechanism of action, has recently been shown to be a sepiapterin reductase (SPR) inhibitor. SPR is part of the BH4 synthesis cascade and is also upregulated by nerve injury. Inhibiting SPR will reduce BH4 levels and therefore should act as an analgesic. We propose SSZ as a novel anti-neuropathic pain medicine.